Ontogenisis of Merkel-cell carcinoma - Fernanda Guimarães Souza; Daniela Pessanha dos Santos; Luiza Oliveira Ribeiro; Thiago Rubim Batista Bellot Nascimento; Flávio Barbosa Luz (Surgical & Cosmetic Dermatology)
A narrative review was performed to clarify the ontogenesis of Merkel-cell carcinoma. It is hypothesized that the cells are derived from the embryonic neural crest, skin stem cells, epithelial cells, pre-/pro-B cells, dermal fibroblasts, or metastatic cells from other types of carcinomas. The influence of epigenetics was also considered. Methodologically, to prepare the summary articles were selected from the PubMed and SciELO databases and cited references. The results suggest that it is more likely that Merkel-cell carcinoma has multiple origins, possibly from poorly differentiated cells.